Practical Approach to Predicting the K0 Behavior of In Situ Sandy Gravel - Ming-Jie Jiang; Jun-Gao Zhu; En-yue Ji; Ying-qi Wei; Zhi-zhou Geng (Advances in Civil Engineering)
To investigate the scale effect on at-rest earth pressure coefficient K0 for sandy gravel, a number of K0 tests for sandy gravel were performed by using a new-developed large-size K0 apparatus. The test samples with different maximum particle size dM are prepared by different techniques, and the scale effect on K0 behavior of sandy gravels is investigated. It is found that the vertical stress σ′v, preparation technique and dM all have some influence on the value of K0 for the tested sandy gravels. Since different dM or preparation techniques all induce the scale effect, the scale effect on K0 of sandy gravel can not be ignored. Based on the test data of sandy gravel, a description of K0 considering scale effect as well as σv′ is proposed and an approach to predict the K0 behavior of sandy gravel in situ is obtained. Furthermore, the accuracy and applicability of the approach is verified.